Medical abortion via telemedicine for women and adolescents: Experience from Moldova. Issue 1 (16th May 2022) - Comendant, Rodica; Cook, Clayborne; Hodorogea, Stelian; Sagaidac, Irina; Bubulici, Cristina; Platais, Ingrida
Abstract: Introduction: To pilot and evaluate the safety and participant satisfaction of the first‐ever telemedicine medical abortion service provided in Moldova, a lower‐income country located in Eastern Europe. Methods: Before enrolment, each participant confirmed their pregnancy with a urine pregnancy test, ultrasound and/or blood test and calculated the gestational age based on the last menstrual period. After study consent was obtained, the study clinician confirmed eligibility for medical abortion and the study and provided counselling via videoconference or telephone. Eligible participants received medications by mail or prescription. A follow‐up call to assess abortion outcome, adverse events and other medical history was conducted 1 week after participants took mifepristone. A pregnancy test was taken 4 weeks after taking mifepristone for a final evaluation of the abortion outcome. The analysis was descriptive. Results: Between March 2020 and March 2021, 549 eligibility screenings were conducted, and 531 study packages containing medications or prescriptions were sent to pregnant women and adolescents with gestations ≤9 weeks since the last menstrual period. The majority of procedures ( n  = 477, 89.8%) were completed without an in‐person visit. Final abortion outcome was available for 499/531 (94.0%) medical abortion procedures: 484/499 (97.0%) were complete abortions, 11 (2.2%) were surgical completions (seven incomplete abortions and four continuing pregnancies), and four participants (0.8%) decided to keep their pregnancy. One serious adverse event occurred. Acceptability of the service was high (99.0% very satisfied or satisfied) and 86.5% of participants reported a future preference for telemedicine. The most commonly reported reasons for choosing the telemedicine service were convenience ( n  = 286, 56.2%) and confidentiality ( n  = 202, 39.7%). Conclusion: The medical abortion via telemedicine service has proven to be a safe and acceptable option for women and adolescents in Moldova. This model has the potential to increase access to abortion, including during emergencies like the COVID‐19 pandemic. Practitioner Points: Telemedicine medical abortion should continue to be provided in Moldova as a possible alternative to in‐person abortion care.